2013
DOI: 10.1002/pip.2379
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a 7‐kW crystalline silicon generator after 17 years of operation in Madrid

Abstract: The degradation observed on a 7-kWp Si-x photovoltaic array after 17 years of exposure on the roof of the Solar Energy Institute of the Polytechnic University of Madrid is presented. The mean peak power degradation has been 9% over this time, or an equivalent to 0.53% per year, whereas peak power standard deviation has remained constant. The main visual defects are backsheet delamination at the polyester/polyvinyl fluoride outer interface and cracks in the terminal boxes and at the joint between the frame and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…A number of researchers have undertaken, over the years, to study the long-term outdoor performance, degradation and failure of solar PV modules around the world. Notable authors in this area include Lorenzo et al [36], Bandou et al [37], Ndiaye et al [38], Jordan and Kurtz [18], Quintana et al [39], Skoczek [40], Skoczek et al [41], Kahoul et al [42] and Ferrara and Daniel [43]. The literature identifies major causes and modes of module degradation and failure to include [18,39]: degradation of packaging materials, loss of adhesion, degradation of cell/module interconnects as a result of thermomechanical fatigue, degradation due to moisture intrusion and degradation of semiconductor device [39].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have undertaken, over the years, to study the long-term outdoor performance, degradation and failure of solar PV modules around the world. Notable authors in this area include Lorenzo et al [36], Bandou et al [37], Ndiaye et al [38], Jordan and Kurtz [18], Quintana et al [39], Skoczek [40], Skoczek et al [41], Kahoul et al [42] and Ferrara and Daniel [43]. The literature identifies major causes and modes of module degradation and failure to include [18,39]: degradation of packaging materials, loss of adhesion, degradation of cell/module interconnects as a result of thermomechanical fatigue, degradation due to moisture intrusion and degradation of semiconductor device [39].…”
Section: Introductionmentioning
confidence: 99%
“…Gangopadhyay et al 2013;Akarslan 2012;Panasonic HIT 2015;EVOENERGY 2012;Kohler et al 2014;Gottschalg et al 2013; Takahashi et al 2001;Markvart et al 2003;Mayfield 2012;Luque and Hegedus 2003;Kelly and Gibson 2011;Dimova-Malinovska 2010;So et al 2006;Lorenzo et al 2014;Cornaro et al 2015;Broderick et al 2015), while the temperature coefficients of some of the modules are shown in…”
mentioning
confidence: 97%
“…Quite a number of researches have been carried out in the past years on topics related to these failure categories in order to overcome the associated challenges. Notable works from prior work are recorded in some work presented by authors such as Wohlgemuth [20], Wohlgemuth et al [21], [22], Zaman et al [33], Pregeli et al [34], Oozeki et al [35], Voronko et al [36], Lorenzo et al [37], Bandou et al [38], Ndiaye et al [39] and Skoczek et al [40]. The authors reviewed and explored the status duo of PV system reliability using outdoor data from fielded arrays and results from accelerated testing of components [21,[33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Notable works from prior work are recorded in some work presented by authors such as Wohlgemuth [20], Wohlgemuth et al [21], [22], Zaman et al [33], Pregeli et al [34], Oozeki et al [35], Voronko et al [36], Lorenzo et al [37], Bandou et al [38], Ndiaye et al [39] and Skoczek et al [40]. The authors reviewed and explored the status duo of PV system reliability using outdoor data from fielded arrays and results from accelerated testing of components [21,[33][34][35][36][37][38][39][40]. Some authors studied the long-term outdoor performance, degradation and failure of PV systems/modules across the world [18], [22], [35][36][37][38], [40] while other explored the short-term effects (infant-failures) of these systems [33,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation